Ganadevata: hundred Ganesa icons from Vasant Chowdhury in the collection of Indian Museum. - Indian Museum. (Indian Museum, 2011)
Catalog of Ganesh icons from South Asia.
Includes bibliographical references.
Catalog of Ganesh icons from South Asia.
Keywords: Hindu sculpture / Catalogs.; Ga?esa (Hindu deity) / Art / Catalogs.